EFEKTIVITAS ANTIDIABETES EKSTRAK DAUN RAMBUSA (Passiflora foetida L.) PADA MENCIT (Mus musculus) DENGAN INDUKSI GLUKOSA - Khildah Khaerati; Ihwan Ihwan; Musdalifah S Maya (Universitas Tadulako, 2015)
Passiflora foetida leaves used by the society for generations as a natural antidiabetic drug research aims to test the effectiveness of the leaf extract of Passiflora foetida with variations of a dose of 250 mg / kg, 500 mg / kg, and 750 mg / kg in lowering blood sugar levels in mice. Passiflora foetida leaves were extracted by sokhletasi method with 70% ethanol, the extract was tested on 15 mice, the test animals were randomized into 5 groups consist of negative control group given 0.5% Na-CMC, positive control group was given glibenclamide 0, 65 mg / kg, and the treatment group were given the leaf extract of Passiflorafoetida with variations of each dose of 250 mg / kg, 500 mg / kg, 750 mg / kg. To increase blood sugar levels in mice induced glucose 50%. Measurement of blood sugar levels in mice were performed using an easy touch glucometer and blood is taken via the lateral tail vein. The results showed that the percentage of blood sugar levels drop to a negative control is 13.1%, for a dose of 250 mg / kg body weight of 29.52%, for a dose of 500 mg / kg was 38.79%, to dosis750 mg / kg was 49, 21%, and 48.1% for the positive control. The results showed that the leaf extract of Passiflorafoetida at a dose of 750 mg / kg is most effective as an antidiabetic